BREASTFEEDING VS. FORMULA FEEDING: ETHICAL, MEDICAL, AND RELIGIOUS PERSPECTIVES IN INFANT NUTRITION DECISION-MAKING - Syarfaini; surahmawati, Surahmawati; Amansyah, Munawir; Nildawati; Indar (Homes Journal: Hospital Management Studies Journal, 2025)
Background: Breastfeeding is globally recognized as the optimal form of infant nutrition due to its numerous health benefits. However, the decision between breastfeeding and formula feeding presents ethical dilemmas influenced by medical, socio-economic, cultural, and religious factors. The interplay between parental autonomy, healthcare professionals’ responsibilities, and societal norms creates complexities in infant feeding choices. Objective: This study aims to analyze the ethical considerations in breastfeeding and formula feeding decisions, emphasizing parental rights, healthcare responsibilities, and the influence of cultural and religious values. Methods: A literature review was conducted to examine ethical principles, including autonomy, beneficence, and non-maleficence, in the context of infant feeding choices. The study also explored real-world cases where parents opted for formula feeding due to various constraints. Additionally, religious perspectives, particularly from Islamic teachings, were analyzed to understand their role in shaping breastfeeding practices. Results: The findings highlight that while breastfeeding remains the gold standard, formula feeding is sometimes necessary due to medical, economic, or social reasons. Ethical dilemmas arise when parental autonomy conflicts with public health recommendations. Healthcare professionals play a crucial role in providing evidence-based information, supporting informed decision-making, and mitigating societal stigma associated with infant feeding choices. Conclusion: Ethical considerations in infant feeding require a balanced approach that respects parental autonomy while promoting the best interests of the child. Healthcare professionals must ensure that parents receive accurate information and support to make informed decisions. Addressing societal and religious influences is essential in fostering an inclusive and supportive environment for all feeding choices.